Dálkové monitorování teploty - Kvarda, Tomáš (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2009)
Práce se zaměřuje na navržení systému pro měření teploty v kryokabině s přesností ±2°C. Návrh spočívá ve výběru vhodného senzoru, příslušného měřícího obvodu, A/D převodníku a zobrazovací jednotky. Poslední částí je návrh vyhřívacího obvodu.

This thesis is concerned on making project of temperature measuring system in cryochamber with an accuracy of ±2°C. The project consists of selection of suitable sensor, competent measuring circuit, A/D converter and display. The last section consists of project of heating circuit.
Telemetric temperature measurement
Keywords: Měření nízkých teplot; kryokabina; kryoterapie; teplotní snímač; RTD; A/D převodník; vyhřívací obvod; XTR105; Pt100; This thesis is concerned on making project of temperature measuring system in cryochamber with an accuracy of ±2°C. The project consists of selection of suitable sensor; competent measuring circuit; A/D converter and display. The last section consists of project of heating circuit.